2022
DOI: 10.1177/08862605221120893
|View full text |Cite
|
Sign up to set email alerts
|

Intra-Urban Variation of Intimate Partner Violence Against Women and Men in Kenya: Evidence from the 2014 Kenya Demographic and Health Survey

Abstract: Although urban areas are diverse and urban inequities are well documented, surveys commonly differentiate intimate partner violence (IPV) rates only by urban versus rural residence. This study compared rates of current IPV victimization among women and men by urban residence (informal and formal settlements). Data from the 2014 Kenya Demographic and Health Survey, consisting of an ever-married sample of 1,613 women (age 15–49 years) and 1,321 men (age 15–54 years), were analyzed. Multilevel logistic regression… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 59 publications
0
5
0
Order By: Relevance
“…Women in informal settlements face several political, economic, social, environmental, and climatic factors that may contribute to stress and, in turn, impact sleep quality. Studies have shown that rates of interpersonal violence and common mental health issues are much higher for women in informal settlements in Kenya than in other populations in the nation (28, [40][41][42]. Research also suggests that women in informal settlements have the worst health outcomes of any population in Kenya (43).…”
Section: Discussionmentioning
confidence: 99%
“…Women in informal settlements face several political, economic, social, environmental, and climatic factors that may contribute to stress and, in turn, impact sleep quality. Studies have shown that rates of interpersonal violence and common mental health issues are much higher for women in informal settlements in Kenya than in other populations in the nation (28, [40][41][42]. Research also suggests that women in informal settlements have the worst health outcomes of any population in Kenya (43).…”
Section: Discussionmentioning
confidence: 99%
“…It highlights an important safeguarding threat to a study on vulnerable girls or women–the ongoing risk of violence. This is critical in communities, such as urban informal settlements, with high rates of violence occurring among 38% of women 5. Sadly, the risk of violence for women and girls in these communities is high whether in the study or not, but study processes may exacerbate risk.…”
Section: Case Study 1: How Participation In a Study Can Expose A Preg...mentioning
confidence: 99%
“…This is critical in communities, such as urban informal settlements, with high rates of violence occurring among 38% of women. 5 Sadly, the risk of violence for women and girls in these communities is high whether in the study or not, but study processes may exacerbate risk. An emerging question is: ‘ Who chooses if a participant should be unenrolled from a study if it emerges that she may be at risk of violence–the researchers or the participants?…”
Section: Case Study 1: How Participation In a Study Can Expose A Preg...mentioning
confidence: 99%
See 2 more Smart Citations